(3OQQ GdJjLGf hZQQ JhGQjN GdReGfs - (3CHh HcQ Hf YHjO Gddg Hf GjHc GdUQNOj GdOGhOGQs ((3jhSa Hf YKeGf GdMejQi s)
(3ChdgG (B:s
(3HMeOc ESJaJM hHQTOc CSJQTO hGSJfLM s
(3BNQgG (B:s
(3fLR GdJGQjN GdeNJUQ hGddg GdMeO hGdefI s
(3hgh JGQjN YGe jfJgi Edi SfI (B710 (3g` eY PcQ JQGLe Gdedhc hGdhRQGA hGddYeGA hGdCOHGA hGdTYQGA hGdCWHGA hZjQges
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B58 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI eUhQI Yf ecJHI CMeO NGf HGSJGfHhd (B(2605) s
Keywords: (3GdJGQjNs